Stability indicating RP-UPLC determination of three antiviral agents: emtricitabine, tenofovir, and rilpivirine in combined pharmaceutical dosage form - Vinutha Kommineni; Spoorthi Pohar; N. Sri Lakshmi; N. Swarna Latha (Future Journal of Pharmaceutical Sciences, 2025)
Abstract Background The concurrent measurement of emtricitabine, tenofovir, and rilpivirine was achieved using UPLC, employing Analytical Quality by Design (AQbD) principles, which encompass response surface methodology (RSM) and Box–Behnken design (BBD). This approach offers a systematic and efficient method for improving analytical procedures and ensuring reliable results. Results Analyte separation was accomplished using an Endoversil C 18 (2.1 × 50 mm, 1.7 µm) column as the stationary phase. The mobile phase consisted of a mixture of 80% orthophosphoric acid (0.1%) and 20% acetonitrile, with a flow rate of 0.4 ml/min and a column temperature of 30 °C. A photodiode array detector was used for detection at 270 nm. The peak area response-concentration curve exhibited linearity across ranges of 50–250 µg/ml (emtricitabine), 100–500 µg/ml (tenofovir), and 10–50 µg/ml (rilpivirine). Quantitation limits were determined to be 0.099 µg/ml (emtricitabine), 0.165 µg/ml (tenofovir), and 0.066 µg/ml (rilpivirine). The method was successfully validated for the simultaneous determination of emtricitabine, tenofovir, and rilpivirine in combined tablet dosage form. Percentage recoveries were 99.89%, 99.52%, and 100.20%, with relative standard deviations of 0.415%, 0.268%, and 0.559% for emtricitabine, tenofovir, and rilpivirine, respectively. Conclusion The performance of the proposed method was evaluated against reported RP-UPLC methods and found to be rapid and cost-effective. The developed and validated stability indicating RP-UPLC method proved suitable for quality control and drug analysis.